Genetic variants in telomerase-associated protein 1 are associated with telomere damage in PAH-exposed workers - Xiaoran Duan; Hongmei Wang; Yongli Yang; Pengpeng Wang; Hui Zhang; Bin Liu; Wan Wei; Wu Yao; Xiaoshan Zhou; Jie Zhao; Wei Wang (Ecotoxicology and Environmental Safety, 2021)
Telomeres are functional complexes at the ends of linear chromosomes, and telomerase aids in their maintenance and replication. Additionally, accumulating evidence suggests that telomerase-associated protein 1 (TEP1) is a component of the telomerase ribonucleoprotein complex and is responsible for catalyzing the addition of new synthetic telomere sequences to chromosome ends. In our previous study, we found that genetic variants of the TERT gene participated in the regulation of telomere length. Exposure to particulate matter, environmental pollutants, oxidative stress, and pesticides is associated with shortening of telomere length. However, it is unknown whether genetic variants in the TEP1 gene may affect telomere length (TL) in polycyclic aromatic hydrocarbon (PAH)-exposed workers. Therefore, we measured the peripheral leukocyte TL and genotyped the polymorphism loci in the TEP1 gene among 544 PAH-exposed workers and 238 healthy controls. Covariance analysis showed that the individuals carrying TEP1 rs1760903 CC and TEP1 rs1760904 TT had longer TL in the control group (P < 0.05). In the generalized linear model, we found that rs1760903 CC was a protective factor against TL shortening, and PAH exposure could promote telomere shortening (P < 0.05). Thus, this study reinforces the roles of environmental factors and genetic variations in telomere damage, and provides a theoretical foundation for the early detection of susceptible populations and the establishment of occupational standards.